Rural Triatoma rubrovaria from southern Brazil Harbors Trypanosoma cruzi of lineage IIc - Martins, Luciamáre P. A.; Marcili, Arlei; Castanho, Roberto E. P.; Therezo, Altino L. S.; De Oliveira, Janaína C. P.; Suzuki, Rodrigo B.; Teixeira, Marta M. G.; Da Rosa, João A.; Sperança, Márcia A. (American Society of Tropical Medicine and Hygiene, 2008)
Triatoma infestans, the main vector of Chagas disease, has nearly been eliminated from Brazil. Nevertheless, other triatominae species are involved in the domiciliation process, including Triatoma rubrovaria in Rio Grande do Sul State (RS). Previous studies showed that 1.6% of the T. rubrovaria specimens collected at the rural district of Quaraí, RS, were naturally infected by Trypanosoma cruzi. In this study, five T. cruzi isolates obtained from infected triatomines were characterized molecularly and biologically. Genotyping of the T. cruzi isolates showed that they belong to lineage IIc of T. cruzi (TCIIc). Biological characterization showed miotropism and myositis during acute and chronic phases of infection, respectively. Virulence and mortality rates were variable among isolates. To our knowledge, this study corresponds to the first characterization of T. cruzi isolates from T. rubrovaria and the first description of TCIIc in the sylvatic cycle of T. cruzi from the southern region of Brazil. Copyright © 2008 by The American Society of Tropical Medicine and Hygiene.